Answer:
-2.61803398875, -0.38196601125
or
(-3±√5)/2
Step-by-step explanation:
First, expand. (2x+3)² = 4x²+12x+9=5
4x²+12x+4 = 0
Quadratic equations take the form ax²+bx+c = 0
In this case,
a = 4
b = 12
c = 4
You can solve with the equation x=(-b±√b²-4ac)/2a
Plug in:
(-12±√144-64)/8
(-12±√80)/8
(-12±√2^4×5)/8
(-12±4√5)/8
(-3±√5)/2
Final answer x = (-3±√5)/2
If you want decimal form: -2.61803398875, -0.38196601125
The simplified expression of
is ![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
<h3>How to simplify the expression?</h3>
The expression is given as:
![\sqrt{\frac{162x^9}{2x^{27}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B162x%5E9%7D%7B2x%5E%7B27%7D%7D%7D)
Divide 162 and 2 by 2
![\sqrt{\frac{81x^9}{x^{27}}}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B81x%5E9%7D%7Bx%5E%7B27%7D%7D%7D)
Take the square root of 81
![9\sqrt{\frac{x^9}{x^{27}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7Bx%5E9%7D%7Bx%5E%7B27%7D%7D%7D)
Apply the quotient rule of indices
![9\sqrt{\frac{1}{x^{27-9}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7B1%7D%7Bx%5E%7B27-9%7D%7D%7D)
Evaluate the difference
![9\sqrt{\frac{1}{x^{18}}}](https://tex.z-dn.net/?f=9%5Csqrt%7B%5Cfrac%7B1%7D%7Bx%5E%7B18%7D%7D%7D)
Take the square root of x^18
![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
Hence, the simplified expression of
is ![\frac{9}{x^9}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx%5E9%7D)
Read more about expressions at:
brainly.com/question/723406
#SPJ1
Hello <u>Queengirl0 </u>
Past tense:
Melissa has a full chocolate bar 8/8
At lunch:
Melissa ate 2/8 of the candy bar, 8/8 - 2/8 = 6/8
After school:
Melissa ate 3/8 of the candy bar, 6/8 - 3/8 = 3/8
<u><em>Melissa has 3/8 of a chocolate bar left</em></u>
:)